1998
DOI: 10.1111/j.1346-8138.1998.tb02384.x
|View full text |Cite
|
Sign up to set email alerts
|

The Proliferation and Differentiation of Neonatal Epidermal Melanocytes in F1 Hairless Mice of HR‐1 × HR/De in Serum‐Free Culture

Abstract: To investigate the characteristics of the proliferation and differentiation of epidermal melanocytes in F1 hairless mice of HR-1 x HR/De parents in vitro, cell suspensions of the neonatal epidermis were cultured in a serum-free medium supplemented with dibutyryl adenosine 3',5'-cyclic monophosphate (DBcAMP) and/or basic fibroblast growth factor (bFGF). The differentiation of melanocytes was induced by treatment with DBcAMP. In contrast, the sustained proliferation of melanoblasts was induced by combined treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
(27 reference statements)
2
13
0
Order By: Relevance
“…Our previous study indicated that melanoblasts exist in primary-cultured epidermal cell suspensions derived from the same hairless mouse strain [27]. This hairless mouse characteristically possesses many melanoblasts in the epidermis of neonatal [24] and adult [27] skin and the melanoblasts proliferate well in culture. The study of melanocyte stem cells in this hairless mouse may contribute to our understanding of the mechanisms of the existence and maintenance of human stem cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous study indicated that melanoblasts exist in primary-cultured epidermal cell suspensions derived from the same hairless mouse strain [27]. This hairless mouse characteristically possesses many melanoblasts in the epidermis of neonatal [24] and adult [27] skin and the melanoblasts proliferate well in culture. The study of melanocyte stem cells in this hairless mouse may contribute to our understanding of the mechanisms of the existence and maintenance of human stem cells.…”
Section: Discussionmentioning
confidence: 98%
“…Naganuma et al [23] reported that repeated UVBexposures induce pigmented spots in Hos:(HR-1 Â HR/De)F 1 mice long after the cessation of irradiation. Hos:(HR-1 Â HR/De)F 1 mice have many melanocytes in the epidermis [24] and are suitable for the study of melanocyte function. Pigmented spots induced by UV irradiation in mice may be a good animal model for human lentigines and freckles.…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal cell suspensions from the control and from the UV‐irradiated skins were cultured with 2 ml MDMD2 for 2 d. At this time, cultures consisted of numerous keratinocyte colonies. They were then provided with 1 ml of fresh MDMD2, incubated for another 2 d, and the resulting culture media from multiple paired dishes (6–11) were collected with a Pasteur pipette and stored in plastic centrifuge tubes (Becton Dickinson) at −80°C. Similarly, culture media from 4 to 6 and 6 to 8 d (increase in the size and number of keratinocyte colonies as well as the initiation of melanocyte proliferation) were collected.…”
Section: Elisamentioning
confidence: 99%
“…Disaggregated epidermal cell suspensions derived from the control and from the UV-irradiated mice were cultured in MDMD2. Culture media from multiple paired dishes (6)(7)(8)(9)(10)(11) were collected and assayed for GM-CSF using an ELISA Kit. As shown in Fig.…”
Section: Detection Of Gm-csf In Culture Mediamentioning
confidence: 99%
“…Their poor growth has been attributed to faulty MSH responsiveness and decreased survival. Accordingly, current protocols for culturing primary murine melanocytes rely on pharmacologic manipulation of intracellular cAMP with α-MSH (either in recombinant form or as bovine pituitary extract), dibutyryl cAMP, cholera toxin and/or IBMX (Boissy and Halaban 1985; Halaban et al 1986; Abdel-Malek et al 1992; Furuya et al 1998) as well as stimulation of the protein kinase C pathway with phorbol esters (Kitano 1976; Pittelkow and Shipley 1989). Even with the use of these agents, however, the growth rate of Mc1r -defective melanocytes is delayed when compared to melanocytes with intact MC1R signaling suggesting that MC1R is involved in cell growth in ways other than by simply raising cytoplasmic cAMP levels (Abdel-Malek et al 1995; Suzuki et al 1996).…”
mentioning
confidence: 99%